KRISIS LITERASI DALAM PENDIDIKAN BAHASA INDONESIA: ANALISIS KONSTRUKSI MAKNA MEMBACA PADA GENERASI Z - Sri Ramadhani (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2025)
This study is motivated by the literacy crisis in Indonesian language education, reflected in the low level of critical reading skills among Generation Z students. Exposure to digital media has shaped fast and surface-level reading habits, leading to shallow text interpretation. The study aims to analyze how Generation Z constructs the meaning of reading in Indonesian language learning and to identify factors influencing this construction. Theoretically, this research contributes to constructivist literacy studies; practically, it offers recommendations for strengthening critical literacy-oriented teaching strategies. This research employs a qualitative approach with a case study design involving 25 eleventh-grade students at a public senior high school in Medan, selected through purposive sampling. Data were collected through in-depth interviews, classroom observations, and analysis of students’ reading assignments. Data analysis was conducted through data reduction, thematic categorization, and interpretative conclusion drawing. The findings indicate that most students perceive reading as an academic obligation oriented toward grades rather than as a reflective process of constructing critical understanding. Fragmented reading patterns influenced by digital content consumption highlight the need for more dialogic and contextual Indonesian language learning strategies.